Shear strength and failure criterion of carbon fiber reinforced coral concrete under combined compression-shear stresses. (28th March 2022) - Liu, Bing; Ye, Junpeng; Liu, Xiaoyan; Lin, Weixin; Deng, Zhiheng; Liu, Qizhou
Highlights: The shear strength of CFRCC under compression-shear stresses was investigated. Failure patterns of CFRCC under various normal stress ratios were examined. CF can enhance the shear strength of coral concrete under compression-shear stresses. Failure criterion models for CFRCC under compression-shear stresses were proposed. Abstract: With the rapid development of the marine industry, the wide application potential of coral concrete (CC) in the construction of islands has been identified. Adding carbon fiber (CF) into CC can improve its mechanical properties and further expand its application scope. Many concrete members, such as corbels, expressways, and deep beams, are usually subjected to combined compression-shear loading during service. This study investigated the shear strength of carbon fiber reinforced coral concrete (CFRCC) under combined compression-shear stresses. A total of 162 specimens with six CF dosages (0.0%, 0.3%, 0.6%, 0.1%, 1.5%, 2.0%), six normal stress ratios (0.0, 0.1, 0.2, 0.4, 0.6, 0.8), and three concrete strength grades (C20, C30, C40) were designed to carry out the test. The results show that with the increase in the normal stress ratio, the spalling of concrete along the main shear crack and the friction trace on the shear failure surface are increasingly apparent, and the shear strength also increases. The addition of CF can diminish the spalling of concrete and improve the shear strength, and the optimum CF dosage is approximately 1.5%. As the uniaxial compressive strength increases, the shear strength increases approximately linearly. Based on the test results, the failure criteria for CFRCCs under compression-shear stresses are proposed and show a good agreement with the test results.